Langgar Lembaga Pendidikan Islam - Pardede, Rizky Nur Zannah; Suryani, Ira; Pohan, Hafsah Winona; Nur'aini, Widya; Aldi, Dwiansyah; Pohan, Afsah Winona (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Langgar (prayer house) or often called musala, according to KBBI in 2018, langgar is a small mosque commonly used as a place for prayer or Quran recitation, but there is no Friday prayer there. Langgar is the oldest Islamic educational institution that has been established and developed in the Islamic community in Indonesia. Langgar is the first Islamic educational institution established before pesantren existed. Langgar has educational elements that form a system that includes caregivers, students, goals, methods, materials, and evaluation. Langgar also has a fairly broad position, which is to help residents solve problems in a container and support the process of studying Islam for Muslim residents.